Kualitas Bakteriologi Escherichia Coli dan Coliform pada Air di Distrik Demta Kabupaten Jayapura Tahun 2022 - Kurniawan, Fajar Bakti; Imbiri, Meidy Johana; Asrori; Alfreda, Yulianus Wisma Krisna; Asrianto; Sahli, Indra Taufik; Hartati, Risda (Jurnal Analis Laboratorium Medik, 2022)
Clean water is water used for daily needs with quality that meets hygiene requirements. Poor environmental sanitation can increase the deposit of microorganisms in water. Water containing microorganisms can cause disease. This study aims to determine the number of Escherichia coli bacteria and groups of coliform bacteria. This research includes laboratory observational research. Water samples were obtained from springs and community shelters. Identification and numeration using the MPN (most probable number) method. The media used were Lactose Broth (LB), Brillian Green Lactose Broth (BGLB) and EC Broth with three tubes. The results of the study identified the presence of Coliform and E.coli bacteria. The numerical results on Coliform show only one sample that meets the quality standards. The results of the numeration of E.coli bacteria, all samples did not meet the quality standards of the Minister of Health Regulation No. 32 of 2017. Bacterial contamination is thought to be the result of community activities using water sources as a place for bathing and washing. The conclusion of this study is that the water used for the daily needs of the people of Demta is contaminated with coliform and E.coli.